Efforts to Improve Student Learning Outcomes in Civics Learning by Applying Powerpoint Learning Media: Classroom Action Research at MIN 4 Jeneponto - Kurniati; Muliati (Journal of Action Research in Islamic Education, 2025)
This study aims to analyze the effectiveness of the use of PowerPoint learning media in improving the learning outcomes of fourth-grade students in PPKn subjects with the material of ethnic and cultural diversity at MIN 4 Jeneponto. The method used in this study is the classroom action research method with a quantitative and qualitative approach. The subjects of the study were fourth-grade students who had difficulty understanding the material conventionally. The use of PowerPoint media was implemented through two learning cycles, with data collection through learning outcome tests, observations, and interviews. The results showed that the application of PowerPoint media can significantly improve student learning outcomes. The average student score increased from before and after the application of PowerPoint media. In addition, students became more active, enthusiastic, and easily understood the material presented with an attractive visual display. In conclusion, the use of PowerPoint learning media can be used as an effective alternative in improving student learning outcomes in PPKn subjects, especially in the material of ethnic and cultural diversity. It is recommended that teachers optimize the use of technology-based media in learning to create a more interactive and interesting classroom atmosphere.